2011
DOI: 10.1021/jm200555r
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Suzuki Coupling of Dihaloheteroaromatic Compounds as a Rapid Strategy To Synthesize Potent Rigid Combretastatin Analogues

Abstract: Combretastatin A-4 (CA-4) is a potent tubulin depolymerizing agent able to inhibit tumor growth and with antivascular effects. Although it is in clinical trials, the search for novel analogues that may display better/different features is still ongoing. In this manuscript we describe the synthesis of novel constrained analogues of CA-4 obtained in only two synthetic steps exploiting a regioselective Suzuki coupling of dihalogenated heteroaromatic and alicyclic compounds. All the compounds synthesized have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…The rationale of the design of active compounds was to retain the appropriate geometry of the two adjacent aryl groups required for potent bioactivity of chemically stable cis-restricted derivatives of CA-4. These were obtained by incorporating the olefinic double bond into vicinally diaryl-substituted fivemember aromatic heterocyclic rings (Table 1), such as pyrazole [67], imidazole [67][68][69], thiazole [70][71][72], furazan (1,2,5-oxadiazole) [73], furan [74,75], thiophene [76,77], isoxazole [78,79], oxazole [67,68,80,81], 1,2,3-thiadiazole [39], triazole [82,83,84,85], 1,2,3,4-tetrazole [70,86] and dioxolane [87]. Replacement of the olefinic bond with a five-member heterocyclic ring allowed the retention of the correct geometric orientation of the two phenyl rings of CA-4, placing them at an appropriate distance for efficient interaction with the colchicine-binding domain on tubulin [35].…”
Section: Other Synthetic Stilbene Derivatives As Tubulin-interactive mentioning
confidence: 99%
“…The rationale of the design of active compounds was to retain the appropriate geometry of the two adjacent aryl groups required for potent bioactivity of chemically stable cis-restricted derivatives of CA-4. These were obtained by incorporating the olefinic double bond into vicinally diaryl-substituted fivemember aromatic heterocyclic rings (Table 1), such as pyrazole [67], imidazole [67][68][69], thiazole [70][71][72], furazan (1,2,5-oxadiazole) [73], furan [74,75], thiophene [76,77], isoxazole [78,79], oxazole [67,68,80,81], 1,2,3-thiadiazole [39], triazole [82,83,84,85], 1,2,3,4-tetrazole [70,86] and dioxolane [87]. Replacement of the olefinic bond with a five-member heterocyclic ring allowed the retention of the correct geometric orientation of the two phenyl rings of CA-4, placing them at an appropriate distance for efficient interaction with the colchicine-binding domain on tubulin [35].…”
Section: Other Synthetic Stilbene Derivatives As Tubulin-interactive mentioning
confidence: 99%
“…[1,2] One such important class of compounds is biaryl thiophenes, which have been successfully used as chemotherapeutic, [3] anti-inflammatory, [4] antibacterial, [5] antifungal, [6] antiviral, [7] antioxidant, [8] insecticidal, [9] anti-nociceptive, [10] anti-tubercular, [11] anti-diabetic [12] and anti-depressant agents, [13] Earlier, the regioselective couplings of dibromothiophenes have been studied in detail, [14,15] Schroter and co-workers revealed in their work that the coupling of 2,4-dibromothiophene can be successfully achieved by following the Suzuki cross-coupling reaction, whereas Kumda or Sonogashira found that the couplings preferably occurs at C-2 position in thiophenes. [2] Varello and co-workers reported the one-pot couplings of 2,4-dibromothiophene through the Suzuki-Miyaura coupling reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Combretastatin A-4 binds to the colchicine (1) domain of tubulin and inhibits microtubule polymerisation, resulting in destabilisation of the microtubule cytoskeleton and inhibition of mitosis. The structural simplicity and potent cytotoxicity of CA-4 has led to the development of analogues of CA-4 as new anticancer agents (Fig.…”
mentioning
confidence: 99%
“…The 3,4,5-trimethoxy group on ring A affects cytotoxic activity and 3-hydroxy-4-methoxy groups on ring B affects binding to tubulin. 1,4,5,8,13 In terms of the spatial relationship, the cis-orientation of the two rings of CA-4 is required for binding in the colchicine-binding site of tubulin. Nevertheless, it is notable that the cis-olefin in CA-4 can convert into the thermodynamically more stable, and inactive, trans-olefin due to its metabolic instability.…”
mentioning
confidence: 99%
See 1 more Smart Citation